Peran Brand Awareness Dalam Memediasi Pengaruh Strategi Digital Marketing Terhadap Loyalitas Pelanggan Pada Usaha Joglo Abah - Umi Sobariyah; Rohimat Nurhasan; Hilman Rismanto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the effect of digital marketing strategies on customer loyalty with brand awareness as a mediating variable in the Joglo Abah souvenir business in Garut Regency. This study uses a quantitative approach with a survey method. The research population consisted of all visitors to Joglo Abah in October, totaling 2,084 people, with a sample size of 96 respondents determined using the Slovin formula and simple random sampling technique. Data collection was conducted through an online questionnaire, which was then analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4.0 software. The results showed that digital marketing strategies had a significant effect on customer loyalty and brand awareness. In addition, brand awareness also has a significant effect on customer loyalty and is proven to be able to significantly mediate the relationship between digital marketing strategies and customer loyalty. These findings confirm that brand awareness plays an important role in strengthening the effectiveness of digital marketing strategies in building customer loyalty. This study is expected to contribute theoretically to the development of digital marketing studies and provide practical input for MSME players in designing more effective and sustainable digital marketing strategies.